Helioseismology. Low degree oscillations of the Sun : From the South Pole to SoHO: (the point of view of an observer) - Grec , Gérard (Известия Крымской астрофизической обсерватории, 2008)
For the GOLF data analysis collaboration with: E. Fossat, M. Lazrek, C.Renaud Calculation of numerical solar models due to: G. Berthomieu, T. Corbard, P. Morel, J. Provost, A. Zaatri.